Quality of life and common mental disorders in truck drivers (Research, Society and Development, 2023)
To evaluate the quality of life and common mental disorder in truck drivers who travel on highways in the Southwest of Paraná. This is a cross-sectional and quantitative field study with the participation of 70 truck drivers. For data collection, three questionnaires were used: the Short Form Health Survey, adapted to Portuguese, validated from the Medical Outcomes Study 36, the Self - Report Questionnaire, version 20, to assess the prevalence of common mental disorders and the instrument for sociodemographic and anthropometric assessment. The prevalence of 8 truck drivers with the possibility of common mental disorder was obtained. In relation to the domains of quality of life, increasing averages were obtained in the scores of general health status, followed by limitation due to physical aspects, limitation due to emotional aspects, domain of pain, vitality, mental health, social aspects and functional capacity. Quality of life was compromised in the domains of general status, limitation due to physical and emotional aspects, which may be related to the work style, which makes it difficult to carry out self-care activities and sociability with family and friends.